Identification of Coliform Bacteria on Ice Crystal in Langsa City - Sitorus, Siti Rahmawati; S. Pandia, Ekariana; Atmaja, Teuku Hadi Wibowo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Water is the second most important element for life after air. Water is a clear liquid, odorless, colorless, and tasteless. Water is a basic need for living creatures, especially drinking water. One way of processing drinking water is by freezing it into ice. Ice cubes are a food that is widely known and is usually considered safe for consumption. Coliform bacteria serve as a general marker of contamination in food and water. Coliform bacteria found in the human body can cause several diseases, including diarrhea. The aim of this research was to confirm the presence of coliform bacteria, measure the level of contamination, and identify the specific type of coliform bacteria that contaminated crystal ice from three ice producers located in Langsa City. This research is descriptive in character. Ice crystal samples were tested using the Most Probable Number (MPN) approach. Furthermore, bacteria were identified through microscopic analysis using the gram staining method and biochemical testing, especially IMViC. Each ice crystal sample showed coliform contamination, exceeding the precautionary limits set out in Minister of Health Regulation number 492 of 2010. The highest amount of contamination was 6 MPN/100mL and the lowest amount of contamination was 4 MPN/100 mL. There were 2 types of coliform bacteria found in this study, namely: Escherichia coli and Enterobacter aeroganes.